2018
DOI: 10.1097/hcr.0000000000000318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inspiratory Muscle Training in the Management of Patients With Asthma

Abstract: These findings suggest that IMT may be an effective modality to enhance respiratory muscle strength, exercise capacity, quality of life, daily living activities, reduced perception of dyspnea, and fatigue in asthmatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 26 publications
4
31
1
10
Order By: Relevance
“…Diaphragmatic breathing increases tidal volume, but studies so far have produced conflicting results in COPD (Gosselink et al, 1995;Yamaguti et al, 2012). Inspiratory muscle training has been shown to decrease dyspnea, increase inspiratory muscle strength, and improve exercise capacity in asthmatic subjects (Duruturk et al, 2018). So far, there is no definitive evidence to support or avoid inspiratory muscle training for asthma (Silva et al, 2013;Shei et al, 2016), therefore, specific respiratory muscle tests and training should be limited to patients carefully selected by clinicians taking into account clinical history.…”
Section: Breathing Retrainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Diaphragmatic breathing increases tidal volume, but studies so far have produced conflicting results in COPD (Gosselink et al, 1995;Yamaguti et al, 2012). Inspiratory muscle training has been shown to decrease dyspnea, increase inspiratory muscle strength, and improve exercise capacity in asthmatic subjects (Duruturk et al, 2018). So far, there is no definitive evidence to support or avoid inspiratory muscle training for asthma (Silva et al, 2013;Shei et al, 2016), therefore, specific respiratory muscle tests and training should be limited to patients carefully selected by clinicians taking into account clinical history.…”
Section: Breathing Retrainingmentioning
confidence: 99%
“…Education (Boudreau et al, 2014;Kew et al, 2016;Levy et al, 2016;Farzandipour et al, 2017;Normansell et al, 2017;Yorke et al, 2017;Donner et al, 2018;Gesinde and Harry, 2018;Schuermans et al, 2018) Increased medication technique and adherence Better asthma control Exercise (Maltais et al, 1997;Porszasz et al, 2005;Luxton et al, 2008;Borg et al, 2010;Eichenberger et al, 2013;Spruit et al, 2013;Franca-Pinto et al, 2015;Lingner et al, 2015;Turk et al, 2017;Sahin and Naz, 2019; Increased muscular endurance and strength Improved QoL Reduced bronchial inflammation, asthma symptoms, and exacerbations Physical activity (Garcia-Aymerich et al, 2009;Eijkemans et al, 2012;Coelho et al, 2018;Panagiotou et al, 2020;Physical Activity On, 2020) Reduced risk of development asthma Breathing retraining (Gosselink et al, 1995;Yamaguti et al, 2012;Duruturk et al, 2018) Increased inspiratory muscle strength Increased exercise capacity Reduced symptoms Breathing exercise (Yang et al, 2016;Bruton et al, 2018) Reduced symptoms Weight loss (Beuther and Sutherland, 2007;Stream and Sutherland, 2012;Sutherland, 2014;Freitas et al, 2017;Ricketts and Cowan, 2019) Better asthma control Reduced symptoms Psychological counseling (Yorke et al, 2017) Improved QoL Reduced anxiety…”
Section: Intervention Study Outcomesmentioning
confidence: 99%
“…It is safe to assume that increased respiratory muscle strength in people with asthma may reduce the intensity of shortness of breath and increase exercise tolerance, and it is possible that muscle loss, including respiratory muscle loss, occurs in patients treated with corticosteroids. The review showed that BMI reduces shortness of breath, increases inspiratory force, reduces fatigue, and improves performance in patients with bronchial asthma [99,100], but there are insufficient studies and volume of subjects to recommend for use. The same opinion is held by Shei R. et al [136] and recommend the development and testing of a standard treatment protocol in a large placebo-controlled, placebocontrolled clinical trial to develop more specific recommendations for BMI as an effective, low-cost adjunctive rehabilitation method for asthma patients.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to breathing exercises is to train the inspiratory muscles (BMI) to increase the strength and endurance of the diaphragm and the respiratory muscles. Inspiratory muscle training reduces shortness of breath, increases inspiratory force, reduces fatigue, and improves performance in patients with bronchial asthma [99,100], and is more effective in combination with chiropractic and exercise [101]. Systematic reviews of the effectiveness of inspiratory muscle training in adults with bronchial asthma show that the evidence for its use has been inconclusive [102,103].…”
Section: Elimination Of Allergensmentioning
confidence: 99%
“…В результате хронической резистивной нагрузки на ДМ последовательно развиваются их гиперфункция, гипертрофия и недостаточность, вследствие чего они становятся неспособными к адекватной реализации насосной функции [1]. При стабильной контролируемой БА у больных обычно не наблюдается заметного снижения силовых характеристик ДМ, в то время как у пациентов с тяжелой неконтролируемой БА снижение показателей MIP может достигать 27% от должных величин, а MEP -34% [11]. Основной причиной развития дисфункции ДМ у больных ХОБЛ считают взаимодействие локальных и системных факторов заболевания, изменяющих функционально-метаболический статус мышечных волокон [20].…”
unclassified